Pengaruh Promosi Online Dan Harga Terhadap Keputusan Pembelian Sambal Bawang Baby Cumi Pada Media Sosial Instagram Ms.Kekinian Samarinda - Sarwo Edi Wibowo, Fitri Aldina Mardiana 2 (EKONOMIA, 2021)
The purpose of this study is to know effect of Online Promotion and Price on the Purchase Decision of Chili Sauce Onion Baby Squid on Social Media Instagram Ms.Kekinian Samarinda.The theory used in this research is online promotion, price and purchasing decisions. This research was conducted to consumers who buy chili sauce onion baby squid on social media instagram Ms.Kekinian Samarinda, Population in this study is known and samples taken 100 respondents with probability sampling method with simple random sampling techniques or simple random. Data collection is done by distributing online questionnaires from Google forms using a Likert scale to measure each indicator. The analytical tool used is multiple linear regression.The results of the research on the f test show that online promotion variables and prices together influence the Purchase Decision of Chili Sauce Onion Baby Squid on Social Media Instagram Ms.Kekinian Samarinda